2013
DOI: 10.1097/scs.0b013e318256657c
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Recombinant Human Bone Morphogenetic Protein 2 on Cranial Defect Closure in the Pediatric Population

Abstract: Bone morphogenetic protein 2 may increase the amplitude and uptake of cranial bone grafts in cranial defect closure. This study shows that defect sizes of up to 16 cm can be reliably closed using this technique. Postoperative fusion of uninvolved sutures in 2 patients indicates that rhBMP-2 may have unreported adverse effects; consideration of this finding should be weighed against the benefit of improved closure of calvarial defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…4 However, extended clinical use of BMP-2/ACS has revealed increasing concerns regarding inflammation-related adverse events such as soft-tissue swelling, 5, 6 seroma, 7, 8 bone resorption, 9 and the low osteoinductive efficacy of BMP-2. 4, 10, 11, 12 These complications have resulted in unsatisfactory long-term outcomes in clinical applications. 4, 13, 14 …”
mentioning
confidence: 99%
“…4 However, extended clinical use of BMP-2/ACS has revealed increasing concerns regarding inflammation-related adverse events such as soft-tissue swelling, 5, 6 seroma, 7, 8 bone resorption, 9 and the low osteoinductive efficacy of BMP-2. 4, 10, 11, 12 These complications have resulted in unsatisfactory long-term outcomes in clinical applications. 4, 13, 14 …”
mentioning
confidence: 99%
“…Spinal surgery 27-34 rhBMP-2 may not have clinical advantage over bone grafts in spine fusion due to associated harm. Paediatric use 21,22 BMP-2 has been shown to be successful in the treatment of spinal fusion with a 100% fusion rate in paediatric patients.…”
Section: Bmp-2: Usesmentioning
confidence: 99%
“…More studies are required to determine safe doses and long-term effects for children Paediatric: cranial defect closures [22] 36 Humans A slight higher closure rate compared to control group, no report of brain oedema, herniation and airway problems More studies are required to determine safe doses and long-term effects for children promote healing, but is associated with high patient morbidity and decreased quality of life. [15] Govender et al [15] carried out a study on 420 patients which showed promising results.…”
Section: Needs Further Research In Human Trialsmentioning
confidence: 99%
See 2 more Smart Citations